Poor nutrition doubles post-COVID-19 syndrome risk in cancer patients: insights from a Chinese multicentre study - Zhang, Liangyuan; Yu, Haihang; Yang, Jianzhou; Su, Rila; Zhang, Jiaqi; Zeng, Rongbiao; Liu, Yajie; Zhang, Lei; Xu, Junjie (Frontiers in Nutrition, 2024)
Background: Since 2019, approximately 760 million SARS-CoV-2 cases have been reported globally, with post-COVID-19 syndrome posing significant challenges for cancer patients due to their immunosuppressed status and poor nutritional conditions. The role of nutritional status in influencing their infection risk and post-COVID-19 outcomes remains unclear, underscoring the need for targeted research and strategies. Objective: To investigate the impact of baseline nutritional status on SARS-CoV-2 infection and the risk of post-COVID-19 syndrome in cancer patients. Methods: A multicenter cross-sectional study was conducted from December 2022 to June 2023 in four tertiary hospitals across China. Cancer inpatients aged 18 years and older were enrolled and classified into two groups based on their Nutritional Risk Screening (NRS) scores. The correlation between SARS-CoV-2 infection, post-COVID-19 syndrome and nutritional status were analyzed using multivariable logistic regression.Results: Among 834 eligible cancer patients, 10.8% were in the high nutritional risk group (NRS ≥ 3). The prevalence of SARS-CoV-2 infection was 58.8% (95% confidence interval, CI: 56.8%-60.8%), and post-COVID-19 syndrome was 21.0% (95% CI: 10.4%-14.4%). After adjusting for confounding factors, the high nutritional risk group had a significantly higher prevalence of post-COVID-19 syndrome compared to the low nutritional risk group (32.7% vs. 19.5%, AOR: 2.37, 95% CI: 1.23-4.54, P=0.010). However, no significant difference in SARS-CoV-2 infection rates was found between the two groups (61.1% vs. 58.5%, AOR: 1.12, 95% CI: 0.70-1.80; P=0.634).Interpretation: Poor baseline nutritional status in cancer patients is associated with a higher prevalence of post-COVID-19 syndrome, providing preliminary information on post-COVID-19 syndrome in this population. These findings underscore the importance of adequate nutritional management in cancer patients, particularly during pandemic recurrences.